Er3+/Yb3+ co-doped bioactive glasses with up-conversion luminescence prepared by containerless processing. Issue 11 (15th August 2016) - Li, Qin; Xing, Min; Chen, Zhi; Wang, Xiaoya; Zhao, Cancan; Qiu, Jianrong; Yu, Jianding; Chang, Jiang
Abstract: Er 3+ /Yb 3+ co-doped bioactive glasses were prepared via containerless processing in an aerodynamic levitation furnace. The as-prepared glasses were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) equipped with energy dispersive X-Ray spectroscopy (EDX). The up-conversion luminescence of as-prepared glasses was measured using an Omni- 3007 spectrometer. Furthermore, the in vitro bioactivity was evaluated by soaking the materials in simulated body fluid, and the biocompatibility was evaluated in MC3T3-E1 cell culture. The results show that containerless processing is a unique method to prepare homogeneous rare earth doped bioactive glasses. The obtained Er 3+ /Yb 3+ co-doped glasses show green and red up-conversion luminescence at the excitation of 980 nm laser. The XRD analysis confirmed that calcium silicate powders, as starting materials, were completely transformed from the original multi-crystalline phase (CS-P) into the amorphous-glassy phase (CS-G, EYS, LCS) via containerless processing. The SEM observation combined with EDX and FTIR analyses showed that the as-prepared glasses were bioactive. The cell proliferation assay also revealed that the as-prepared glasses were biocompatible and nontoxic to MC3T3-E1 cells. This study suggests that the luminescent bioactive glasses prepared by containerless processing could be used for studying biodegradation of bone implantation materials.